Analisis Keterampilan Membaca Peserta Didik Kelas IV Pada Pembelajaran Bahasa Indonesia di SD Muhammadiyah Kadisoka Yogyakarta - Nuranisa, Aprilda; Riyanto, Sugeng (Educational Consultant & Counseling Career (EC3) Mataram, 2023)
The habit of students in reading activities is the main thing that will have an impact on the continuation of students in facing a growing future. There are still many students when reading a text in a book, there are still many students who look difficult, especially if students are instructed to rewrite important information obtained from the reading text so that students are confused and always ask the teacher. So that most of the students just re-copy without knowing what the meaning of the text they have written. This research is a qualitative descriptive study. The data collection method used interview, observation, and documentation techniques. The data analysis technique used data triangulation and method triangulation. Technical data analysis using Mils and Huberman. The subjects in this study were classroom teachers and fourth grade students at SD Muhammadiyah Kadisoka Yogyakarta Based on the results of research that has been carried out, the implementation of reading skills in class IV students has been running as it should. At the stages of reading skills the teacher has carried out the teaching and learning process in the classroom.